Crescimento da radioluminescência do ZnO induzido pelo Tm2O3 - Batista, Karoline Ferreira (2019)
Using the radioluminescent property of zinc oxide and aspirating an increase in its RL response by incorporating Tm2O3, the present study presents a promising mechanism for the dosimetry of ionizing radiation. The same one counts on the aid of a ceramic from the mixture of the two oxides resulting in a ceramic that was designated as mixed oxide (ZnO-Tm2O3). Radioluminescence measurements of mixed oxide ceramics and pure ZnO ceramics were performed in order to compare the intensification of the RL response of the samples. By means of two different methods, it was possible to collect the data concerning the radioluminescent emissions of ceramics, while varying the dose absorbed by them (Spectrometer with fiber optic and RGB Radiocolorimetry). From the data obtained for the first method it is possible to verify a double emission RL of the mixed oxide in the blue and green region of the visible spectrum. In the second method, it is possible to observe the behavior of the three components that constitute the RGB color code of the RL emissions, showing a tendency to saturation of the green component and a tendency to the late saturation of the red and blue components. Supporting this, the possibility of detecting radiation for doses ranges higher than those reported in this work. In addition, X-ray diffraction measurements were performed with the purpose of verifying phases alluding to Tm2O3, thus confirming that the ceramic in question is the mixture of the two oxides. Measurements of Raman vibration spectroscopy demonstrate that the ceramic in question presents vibrational modes indicative of oxygen vacancy (VO), thus solidifying the origin of the green luminescence of the ceramic. The thermoluminescence of the mixed oxide ceramic exhibits a major TL peak at approximately 280°C and a peak of lower intensity at 170°C when irradiated within the range of 10-1600 Gy, satisfying the dose-response curve satisfactorily. From the photoluminescence of the mixed oxide ceramics it was possible to verify the intra-configurational transitions 1G4→3H6 and 1D2→3H5 belonging to the thulium ion. From these results it was possible to verify that the blue emission in the RL spectrum originates from the transition 1G4→3H6 of the thulium, as well as the growth of the radioluminescence in the green of the mixed oxide ceramic, can be attributed both the oxygen vacancy present in the matrix of ZnO as well as the 1D2→ 3H5 transitions of the thulium ion composing the Tm2O3 matrix.